ANALISIS PERBAIKAN TEGANGAN DAN RUGI DAYA PADA PENYULANG JETIS PT PLN (PERSERO) UP3 KEDIRI MENGGUNAKAN ETAP 19.0 - Allaam, Hisyam Ghozi; Utomo, Teguh; Hasanah, Rini Nur (Jurnal Mahasiswa TEUB, 2024)
PLN UP3 Kediri is a company that manages the Jetis Feeder distribution channel which is facing voltage drops and power losses. There are several methods to overcome this incident, such as conductor uprating, substation voltage uprating, and capacitor bank installation. With this improvement, it is hoped that the voltage drop and power loss values will be within the range determined according to SPLN (±5% for voltage drop and -10% for power loss) and ETAP alerts will be ±1% of the nominal limit. This research aims to determine the value of voltage drop and power loss before and after the repair method is carried out and determine the most efficient method. This research shows that under existing loading conditions, the Jetis Feeder is in normal condition. Under full load conditions (100%), the Jetis Feeder has a voltage drop of 4.539% and a power loss of 3.182%. The voltage drop value in this condition is still within the safe condition limit according to SPLN, but has entered the alert condition in ETAP, namely >4%. Under these conditions, repair efforts are needed to overcome voltage drops and power losses. After carrying out repair efforts, the voltage drop and power loss values for the 150 mm2 conductor uprating were 4.445% and 5.158%, the priority conductor uprating was 4.135% and 4.658%, the substation voltage uprating was 1.986% and 4.995%, and the capacitor bank installationwas 2 .5% and 4.558%. Keywords – Voltage Drop, Power Loss, Power Flow, ETAP